TI_GERICHTE 52.2019.445 vom 21. August 2019 , Rinnovo di una licenza edilizia di un impianto di telefonia mobile - TI Tribunale d'appello (2019)
Rinnovo di una licenza edilizia di un impianto di telefonia mobile